Mobile 3D Graphics - Malizia, Alessio. (Springer London : Imprint: Springer, 2006)
While advanced 3D graphics techniques – terrain modelling, high-quality texture mapping, advanced lighting and geometry effects, collision detection and image processing - are well understood and supported by industry standards, this is less true in the emerging mobile applications and games market. This book redresses this imbalance, providing an in-depth look at the new OpenGL ES (The Standard for Embedded Accelerated 3D Graphics), and showing what these new embedded systems graphics libraries can provide for 3D graphics and games developers. Historically, not enough was understood about how to deliver a high quality playing experience on handheld, small screen, small memory devices, plus there has been considerable confusion about the hardware’s abilities and restrictions. By addressing these issues this book provides: • A comprehensive explanation of 3D mobile graphics programming • Includes an extensive range of code samples in both C and Java • Combines 3D and 2D mobile graphics methods • Covers recent advances in mobile computer graphics techniques and applications. The book teaches fundamental 3D mobile graphics programming with standard APIs, and covers the basic and advanced application programme interfaces behind the major wireless and mobile devices supporting 3D graphics applications. Advanced undergraduates and postgraduates, as well as mobile application and games developers, will find this an excellent reference source.